2018
DOI: 10.1002/chem.201802691
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Design to Acquire Specificity to Intended G‐Quadruplex Structures

Abstract: A G-quadruplex is a nucleic acid secondary structure that is adopted by guanine-rich sequences, and is considered to be relevant in various pharmacological and biological contexts. G-Quadruplexes have also attracted great attention in the field of DNA nanotechnology because of their extremely high thermal stability and the availability of many defined structures. To date, a large repertory of DNA/RNA G-quadruplex-interactive ligands has been developed by numerous laboratories. Several relevant reviews have als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
119
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(120 citation statements)
references
References 151 publications
1
119
0
Order By: Relevance
“…In this work, we found that our l ‐RNA aptamer, l ‐Ap3‐7, contains an rG4, which is new and interesting. l ‐Ap3‐7’s affinity ( K d ≈100 n m ) is weaker than the G4‐specific antibody BG4 that has a sub‐n m K d , but is comparable to most G4‐specific ligands . Moreover, its ability to distinguish between G4s is encouraging, although we cannot rule out the possibility that it may have some off‐target effect.…”
Section: Figurementioning
confidence: 86%
“…In this work, we found that our l ‐RNA aptamer, l ‐Ap3‐7, contains an rG4, which is new and interesting. l ‐Ap3‐7’s affinity ( K d ≈100 n m ) is weaker than the G4‐specific antibody BG4 that has a sub‐n m K d , but is comparable to most G4‐specific ligands . Moreover, its ability to distinguish between G4s is encouraging, although we cannot rule out the possibility that it may have some off‐target effect.…”
Section: Figurementioning
confidence: 86%
“…The diversity of quadruplex structures will widen with improved methods for detection and evaluation. Such structures will likely change the face of small molecule‐quadruplex targeting as a therapeutic intervention strategy ; these novel RNA structures would likely be exploitative in drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion of G4 DNA binders reported to date have been designed to interact with the external tetrads of G4s via a combination of π–π stacking and electrostatic interactions . Therefore, most G4 binders are planar molecules containing two or more aromatic rings that display strong π–π interactions with the guanine tetrads.…”
Section: Introductionmentioning
confidence: 99%
“…Al arge proportion of G4 DNA bindersr eported to date have been designed to interact with the external tetrads of G4s via ac ombination of p-p stacking and electrostatic interactions. [9,10] Therefore, most G4 bindersare planar molecules con- taining two or more aromatic rings that display strong p-p interactions with the guanine tetrads. In addition, most of these compounds also feature substituents with positive charges which increase their affinity for the negatively charged DNA.…”
Section: Introductionmentioning
confidence: 99%